FIELD HOCKEY ATHLETES INJURIES: A STUDY WITH THE MASCULINE AND FEMININE BRAZILIAN SELECTIONS (Fiep Bulletin - online, 2014)
The purpose of this descriptive study was to analyze the injuries and the mechanisms of injuries pointed for the athletes of the Brazilian selection of feminine and masculine hockey. Participated of the study 17 females players with average of 18,8+3,95 year-old and practice time of 3,69 ± 3,8 years and 14 male players with average of 18,8±1,3 year-old and practice time of 6,0±4,2 years. As measure instrument was used a questionnaire validated with 93% of validity and 100% of clarity. The data were treated with descriptive statistics and correlation of Pearson with p=0,05. The results show that the females are most injured in the lumbar area (8/39), followed by the fist and hand (7/39) and thigh (6/39). The males presented more injuries in the knee (7/26), followed by the shoulder (5/26), fist and hand (4/26). The female team pointed as largest injuries mechanisms the training excess followed by the posture adopted for the game (previous flexion of the trunk). The male team mentioned all the injuries mechanisms that the feminine team, increasing the defensive and offensive actions during game. Most of athletes use preventive equipment and prioritize the quality of the footwear. There was no relationship among number of injuries and the time of practice (rc=0,32;0,22 - feminine; and rc=-0,20;0,05 - masculine) and with the players' age (rc=-0,05;0,86 - feminine; and rc=-0,016;0,96 - masculine). This results emerge for improvement initiatives so much of the physical conditioning, accomplishing a compensatory muscular work, as for the improvement of the athletes' technical level, for to reduce the deleterious effects caused by the mechanical solicitations of the modality.
Keywords: field hockey; injuries; injuries causes